2021
DOI: 10.3389/fcvm.2021.773314
|View full text |Cite
|
Sign up to set email alerts
|

miR-208a in Cardiac Hypertrophy and Remodeling

Abstract: Various stresses, including pressure overload and myocardial stretch, can trigger cardiac remodeling and result in heart diseases. The disorders are associated with high risk of morbidity and mortality and are among the major health problems in the world. MicroRNAs, a class of ~22nt-long small non-coding RNAs, have been found to participate in regulating heart development and function. One of them, miR-208a, a cardiac-specific microRNA, plays key role(s) in modulating gene expression in the heart, and is invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…observed that patients with CCM had a significantly lower relative expression of miR-208a, measured in human myocardial samples, than healthy controls ( Ferreira et al., 2014 ). MiR-208a represents an essential regulator of several pathways involved in cardiac fibrosis and hypertrophy, being also associated with the development of conduction abnormalities and arrhythmias ( Wang et al., 2014 ; Huang et al., 2021 ). Although the role of this microRNA in CD is not clear, published evidence suggests that TGF-β may activate miR-208a to regulate genes related to hypertrophy, as TGF-β neutralizing antibody therapy attenuated miR-208a induced expression in myocytes ( Wang et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…observed that patients with CCM had a significantly lower relative expression of miR-208a, measured in human myocardial samples, than healthy controls ( Ferreira et al., 2014 ). MiR-208a represents an essential regulator of several pathways involved in cardiac fibrosis and hypertrophy, being also associated with the development of conduction abnormalities and arrhythmias ( Wang et al., 2014 ; Huang et al., 2021 ). Although the role of this microRNA in CD is not clear, published evidence suggests that TGF-β may activate miR-208a to regulate genes related to hypertrophy, as TGF-β neutralizing antibody therapy attenuated miR-208a induced expression in myocytes ( Wang et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, miR-208a was among the most abundant circulating EV-derived miRNAs detected in both models. Albeit considered a specific cardiac miRNA, miR-208a is also a known regulator of myostatin , together with miR-208b and miR-499 ( 49 , 50 ), implying a potential role in driving skeletal muscle hypertrophy that thus far remained unexplored. This work proposes miR-208a as an additional modulator of myogenic commitment of progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Except for miR-206, the other six myomiRs, miR-1, miR-133a, miR-133b, miR-208a, miR-208b, and miR-499, can be expressed in cardiac muscles. Moreover, multiple studies have demonstrated that these myomiRs are involved in the development of different types of heart diseases, including dilated cardiomyopathy ( 33 ), coronary artery disease ( 34 ), cardiac hypertrophy ( 35 , 36 ), and myocardial fibrosis ( 37 , 38 ). Although miR-208a and miR-208b were not remarkably higher in the sera of cardiac involvement patients, we believe this may suggest that miR-1, miR-133a, miR-133b, and miR-499 are more sensitive to cardiac involvement.…”
Section: Discussionmentioning
confidence: 99%